2006
DOI: 10.1007/s00122-006-0219-0
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid lethality in interspecific hybrids between Nicotiana tabacum and N. suaveolens: evidence that the Q chromosome causes hybrid lethality based on Q-chromosome-specific DNA markers

Abstract: Hybrid seedlings from the cross Nicotiana tabacum x N. suaveolens express lethality at 28 degrees C. We carried out a cross between monosomic lines of N. tabacum lacking the Q chromosome and N. suaveolens by test-tube pollination and ovule culture at 28 degrees C. To suppress hybrid lethality, hybrid seedlings obtained were transferred to 36 degrees C immediately after germination and cultured. We determined whether Q-chromosome-specific DNA markers were detected among hybrid seedlings. When hybrid seedlings c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
39
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(42 citation statements)
references
References 25 publications
2
39
1
Order By: Relevance
“…Two Q-chromosome-speciWc DNA markers, QCS2 and QCS3, were detected as previously described Tezuka and Marubashi 2006b). …”
Section: Pcr Analysismentioning
confidence: 99%
“…Two Q-chromosome-speciWc DNA markers, QCS2 and QCS3, were detected as previously described Tezuka and Marubashi 2006b). …”
Section: Pcr Analysismentioning
confidence: 99%
“…Only when Haplo-Q was crossed with N. suaveolens could viable plants be obtained. Furthermore, when Haplo-Q is crossed with N. suaveolens and the hybrid seedlings cultured at 36°C are transferred to 28°C, those possessing the Q chromosome die and those lacking the Q chromosome do not (Tezuka and Marubashi 2006). In the present study, hybrid seedlings both possessing and lacking the Q chromosome died within 10 days of transfer from 34 to 28°C.…”
Section: Discussionmentioning
confidence: 48%
“…PCR products were separated by electrophoresis on 1.5% agarose gels in TAE buffer and stained with ethidium bromide to visualize DNA bands. The Q-chromosome-specific DNA marker QCS1 was detected as described by Tezuka and Marubashi (2006).…”
Section: Random Amplified Polymorphic Dna (Rapd) Analysis and Detectimentioning
confidence: 99%
See 1 more Smart Citation
“…This provides for another possibility, that the inhibition of cell death was not directly due to an absence of E2 per se from the genome of GTH4S, but rather, caused by the deletion of the neighboring region of the chromosome around this locus. Tezuka and Marubashi (2006) suggested that the Qchromosome which belongs to the S subgenome in N. tabacum was a counterpart for the expression of lethality in the hybrid of N. tabacumϫN. suaveolens.…”
mentioning
confidence: 99%